Analisis Faktor-Faktor Consumer Engagement pada Media Sosial Twitter Cinema XXI - Oktaviana Nur Handayaningrum (Universitas Negeri Surabaya, 2019)
Cinema XXI is the biggest cinema network in Indonesia. The high number of social media users in Indonesia has made Cinema XXI no longer difficult to embrace all of its customers. Being able to mantain long-term relationships, understanding what consumer wants and needs are important to keep Cinema XXI as the ruler of the cinema market in Indonesia. To do this, Cinema XXI needs to create consumer engagement. Consumer engagement is a marketing investment to create long-term relationship with consumers. Therefore, this research aims to determine what consumer engagement factors were successfully created by Cinema XXI to become the ruler of the cinema market in Indonesia with more than 11 million followers on Twitter social media accounts. By using the Slovin formula, the number of samples in this research were 400 respondents. The factors used amounted to 18 factors obtained from previous research, this reasearch uses quantitative descriptive methods with factor analysis techniques, calculation with SPSS 16. The results of this research state that from the existing dimensions reduced into three new dimensions, namely affective behavioural engagement with sub-dimensional dominance of enjoyment with 0,765, cognitivie behavioural engagement with sub-dimensional dominance of attention with 0,834 and informative engagement with sub-dimensional dominance of up-to-date information with 0,873.